2004
DOI: 10.1002/uog.1012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of maternal plasma volume expansion and antihypertensive treatment with intravenous dihydralazine on fetal and maternal hemodynamics during pre‐eclampsia: a clinical, echo‐Doppler and viscometric study

Abstract: K E Y W O R D S:antihypertensive treatment; maternal whole blood viscosity; plasma volume expansion; pre-eclampsia; umbilical artery pulsatility index; umbilical venous volume flow; uterine artery resistance index ABSTRACT Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Our data confirm the findings of previous studies indicating that, before antihypertensive therapy, uterine artery PI and RI are increased in women with pre‐eclampsia but not in women with gestational hypertension, compared to normotensive controls23, 28–32. The impairment of uteroplacental perfusion found in pre‐eclampsia can explain the less favorable fetal and neonatal outcomes observed in these cases compared with pregnancies complicated by gestational hypertension33–35.…”
Section: Discussionsupporting
confidence: 91%
“…Our data confirm the findings of previous studies indicating that, before antihypertensive therapy, uterine artery PI and RI are increased in women with pre‐eclampsia but not in women with gestational hypertension, compared to normotensive controls23, 28–32. The impairment of uteroplacental perfusion found in pre‐eclampsia can explain the less favorable fetal and neonatal outcomes observed in these cases compared with pregnancies complicated by gestational hypertension33–35.…”
Section: Discussionsupporting
confidence: 91%
“…16 Nevertheless, it has been shown that dihydralazine administration does not result in any change in umbilical venous cross-sectional area, but decreases umbilical artery pulsatility index. 17 No difference in renal volume was found between infants with and without antecedent of antenatal steroids therapy at a single dose. At this point, it has been suggested that fetal glucocorticoids overexposure has a role in the early life programming of adult cardiovascular and metabolic disorders.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that the use of nifedipine therapy decreases maternal blood pressure levels but does not produce significant difference in the RI in either the fetal or uteroplacental vessels 16 . Nevertheless, it has been shown that dihydralazine administration does not result in any change in umbilical venous cross‐sectional area, but decreases umbilical artery pulsatility index 17 …”
Section: Discussionmentioning
confidence: 99%
“…We reported a transient decrease (after 1.5 h hemodialysis) and spontaneous recovery (after 3 h hemodialysis) of umbilical arterial resistance index [27], and this change was thought to be a result of transient maternal hypovolemia. Boito et al reported that the umbilical arterial resistance index decreased with maternal plasma volume following dihydralazine administration expansion in pre-eclamptic patients [28]. They reported that the maternal blood pressure also simultaneously decreased.…”
Section: Umbilical Arterial Blood Flowmentioning
confidence: 96%
“…Antihypertensive agents such as nicardipine [33], niphedipine [34], and methyldopa [35] have reported no significant effects on umbilical arterial flow. However, hydralazine was reported to decrease umbilical arterial pulsatility indices [28,36].…”
Section: Umbilical Arterial Blood Flowmentioning
confidence: 99%